A kollektív bűnösség jegyében : Magyarország és a „németkérdés” – hetven évvel ezelőtt - Orosz, László (Közép-Európai Közlemények, 2017)
Finding its justification in various ideologies – this time in the notion of “Collective Guilt” – the next chapter in a long line of 20th-century ethnic cleansings was initiated seventy years ago, in January 1946: the systemic deportation of a significant portion of Hungary’s ethnic German population. These atrocities, which found their origins in a “crime and punishment”-style collective treatment, impacted Hungary’s Germans to a much greater degree than the country’s general population. This was in easily discernable conjunction with other nations’ efforts at self-exoneration following the end of WWII, which was that culpability for the war lay expressly with the Germans. In the countries occupied by the Soviets, the social and political transformations underway provided a suitable environment for this view to flourish. The presentation wishes to provide context to the events of seventy years ago, to the so-called “German Question”, touching upon the most important domestic and foreign policy dilemmas, the question of land ownership, the emergence of domestic resettlement issues, the Beneš Decrees and the population exchange agreement, the differing view-points of the political parties, the revival of the perception of a hated enemy, the indoctrination of the public and the voices both of reason and of hatred.